2004
DOI: 10.1111/j.0007-1013.2004.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of interactive computer tutorials for an undergraduate mathematical literacy course

Abstract: This article describes a study of learning when students used interactive spreadsheet-based computer tutorials in a mathematical literacy course. It foregrounds theories relating to the role of computer technology (and specifically spreadsheets) as a mediator for learning of mathematics. It outlines the application of quantitative methods involving pre-and post-testing of students, both in the computer laboratory and in the lecture sessions, and discusses factors constraining the experimental design and the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…This view is in accordance with certain previous studies (e.g. Frith et al, 2004) that have found an advantage of spreadsheet-based teaching over traditional teaching methods. Such a comparison could therefore have led, potentially, to one group of students being disadvantaged in terms of their preparation for the test.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This view is in accordance with certain previous studies (e.g. Frith et al, 2004) that have found an advantage of spreadsheet-based teaching over traditional teaching methods. Such a comparison could therefore have led, potentially, to one group of students being disadvantaged in terms of their preparation for the test.…”
Section: Discussionsupporting
confidence: 93%
“…First, although many authors (e.g. Beare, 1993;Drier, 2001;Flynn et al, 2006;Frith et al, 2004;Hall, 1995) have proffered processes that may explain improved outcomes-based performance when using spreadsheet programs to teach statistics (e.g. more realistic and interactive examples, simulation-based activities improving understanding, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at home, the majority of students are connecting to the Internet using high-speed (55.3%) and wireless access (37.5%), and at school, almost half (49.8%) of the respondents indicated using a computer lab to go online. This is important as many instructors are beginning to use multimedia technologies that require fast connectivity speeds to support in-class activities at home (Firth, Jaftha, & Prince, 2004;Dunn, Thomas, Green, & Mick, 2006;Savage, & Vogel, 1996). Students report having access to technology that is capable of handling such complex tasks online, possibly reducing anxieties due to technology malfunctions (Kelsey, 2000).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Educators and researchers have used computer‐based tutorials to teach a variety of subjects and found that this instructional application helps students acquire intended knowledge more effectively and efficiently. The immediate feedback and self‐pacing features inherent to most computer‐based tutorials facilitate the learning process and better prepare students for problem‐solving tasks that are complicated in nature (Baggott, 2000; Frith, Jaftha & Prince, 2004; Rowe & Thorburn, 2000). However, few studies have discussed the motivational component of computer‐based tutorials that is essential when evaluating any instructional material regardless of its format (Newby et al , 2000).…”
Section: Related Studiesmentioning
confidence: 99%